Healthcare Professionals' Responses to Complaints: A Qualitative Interview Study With Patients, Carers and Healthcare Professionals Using the Theoretical Domains Framework and COM‐B Model - Antonopoulou, Vivi; Schenk, Paulina M.; McKinlay, Alison R.; Chadwick, Paul; Meyer, Carly; Gibson, Beckie; Sniehotta, Falko F.; Lorencatto, Fabiana; Vlaev, Ivo; Chater, Angel M. (Health expectations : an international journal of public participation in health care and health policy, 2024)
ABSTRACT Background Patient complaints in healthcare settings can provide feedback for monitoring and improving healthcare services. Behavioural responses to complaints (e.g., talking or apologising to a patient) can influence the trajectory of a complaint for instance, whether a complaint is escalated or not. We aimed to explore healthcare professional (HCP) and service user (patient and carer) views on complaints' management and the perceived factors influencing responses to complaints within a healthcare setting by applying behavioural frameworks. Method A qualitative study was conducted using online or phone‐based interviews with eleven HCPs and seven patients or carers. All participants (N = 18) had experience responding to or submitting a formal complaint in secondary and tertiary public healthcare settings in the United Kingdom. The interviews were structured using the Capability‐Opportunity‐Motivation‐Behaviour (COM‐B) Model. We analysed the transcripts using inductive thematic analysis. Then, themes were deductively mapped onto the COM‐B Model and the more granular Theoretical Domains Framework (TDF). Results Ten themes were generated from the analysis representing the influences on HCPs' responses to complaints from HCP and patient/carer perspectives. This included (with TDF/COM‐B in brackets): ‘Knowledge of complaint procedure’ (Knowledge/Capability), ‘Training and level of skill in complaints handling’ (Skills/Capability), ‘Regulation of emotions associated with complaints’ (Behavioural regulation/Capability), ‘Confidence in handling complaints’ (Beliefs about capabilities/Motivation), ‘Beliefs about the value of complaints’ (Beliefs about consequences/Motivation) and ‘Organisational culture regarding complaints’ (Social influences/Opportunity). Staff highlighted strong support systems and open discussions as part of positive organisational cultures regarding complaints (Social influences/Opportunity), and a lack of certainty around when to treat issues raised by patients as a formal complaint or informal feedback (Knowledge/Capability). Conclusion Our study findings highlight the importance of strong support systems and organisational openness to patient feedback. These findings can be used to design targeted interventions to support more effective responses and enhance patient‐centred approaches to complaints management in healthcare settings. Patient and Public Contribution Patient and public involvement (PPI) was integral in this research. The NIHR PRU in Behavioural and Social Sciences had a dedicated PPI strategy group consisting of six external representatives from the patient and public community (Newcastle University, 2024). These six PPI members actively participated in shaping the research by reviewing and providing feedback on all questionnaire items before the data collection. They were actively involved in supporting participant recruitment by advertising this study on their PPI platform, The VoiceR,1 and through their online social networks. During the analysis stages of the research, preliminary findings were discussed with the PPI group to support ‘sense checking’ and interpretation of the results.